Pemikiran Ekonomi Islam Perspektif Hasan Al Banna - Fathul Khair (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
Contemporary Islamic economics has rapidly developed in recent decades, offering a fair and sustainable alternative to classical and modern economic systems. Several factors that encourage the rise of Islamic economics are; dissatisfaction with classical and modern economic systems; the revival of Islamic values throughout the world as a solution to dissatisfaction with classical and modern economic systems; The Islamic finance industry is growing fast; more countries implementing Islamic economic policies; Muslim scholars began to research and develop Islamic economic theory. One of the Muslim scholars who later became a figure in contemporary Islamic economics was Hasan Al Banna. The purpose of this research is to find out Hasan Al Banna's thoughts on Islamic economics. The discussion method used in this study uses library research or qualitative descriptive. The results of this study show that Hasan Al Banna's thoughts on the economic systems of capitalism, socialism, and communism are not for Muslims. These systems were not born in Muslim countries and were not intended to be applied to Muslim communities. Islam has offered perfect system, a system that leads them towards goodness and pure Islamic guidance that comes from the Qur'an and Sunnah. Because the economic sector is easily reacted to the changing circumstance, the Qur'an gives a global ideal to the problem and enforce rules that guarantee people to get its benefits and avoid its harms.